THE RELATIONSHIPS AMONG PHENOTYPIC BODY INDICES OF LOCAL GOAT - TAHER, TAHER M.; BAMERNY , ARAZ O.; HUSSEIN, REYZAN A. (Journal of Duhok University, 2023)
The relationship between some body indices are significant tools to evaluate the final yield in animals. The present research was carried out in a private farm at Sumeal area, Duhok province, Kurdistan Region, Iraq. The present trial aimed to illustrate the relationships between/among some body indices, in addition to try finding a prediction equation for some complicated body indices. One-way ANOVA, correlation and regression coefficients were analyzed. The results revealed that most body indices differed significantly (p≤0.05) among the studied ages; and the correlation coefficients between of them were also significant (p≤0.05). The stepwise analysis within regression revealed that it may predict with Body ratio (BR) from body (IB) and from weight 3 (Heart girth related), with high significant effect (p≤0.01), but having relatively low coefficient of variation (R2)